Analisis Tingkat Kepuasan Pengguna Whatsapp Sebagai Media Berbagi Informasi Menggunakan Metode Pieces Framework - Diva Putri Harianto; Joy Nashar Utama Jaya; Darmansyah Darmansyah (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
The development of technology in this era brings changes in aspects of people's lives which are followed by the development of social media that makes individuals have the complexity of technological needs. One of the technological needs is the use of the WhatsApp application. WhatsApp is a cross-platform messaging application that allows us to exchange messages using the same internet data plan as email, web browsing, and others. Judging from the various features offered by WhatsApp, it is a unique feature, so this WhatsApp application has become the main medium used by the people of Balikpapan City as a medium of communication and information sharing. To find out the system owned is running well or not, there is a need for an analysis of the level of satisfaction of a system. One method that can be used in analyzing the system is the PIECES Framework where there are 6 indicators (Performance, Information and Data, Economical, Control and Security, Efficiency, and Service) by distributing questionnaires to the people of Balikpapan City, especially North Balikpapan getting 115 respondents. From the results of this study, it shows that WhatsApp gets an average value of 4.31 which shows that users are satisfied in using the WhatsApp application as a medium for sharing information